Hypermobility Frequency in School Children: Relationship With Idiopathic Scoliosis, Age, Sex and Musculoskeletal Problems - Sinem BOZKURT,; Gülseren KAYALAR,; Nihal TEZEL,; Tuba GÜLER,; Bilge KESİKBURUN,; Merve DENİZLİ,; Sefa TAN,; Hürriyet YILMAZ, (Archives of Rheumatology, 2019)
Objectives: This study aims to assess the prevalence of generalized joint hypermobility (GJH) in school children in relation to scoliosis and to identify musculoskeletal problems. Patients and methods: This cross-sectional study included 822 school children (413 males, 409 females; mean age 12.2±1.3 years; range, 10 and 15 years). Demographic characteristics of all children were recorded. The presence of GJH was assessed by the Beighton score (≥4 was considered joint hypermobility). Scoliosis screening consisted of forward bend test (FBT) and measurement of angle of trunk rotation (ATR). Positive FBT or ATR ≥5° was referred to a portable X-ray device. The presence of musculoskeletal complaints was determined by a questionnaire. Results: Children’s Body Mass Index (BMI) was 19.6±4.1. GJH was diagnosed in 151 subjects (18.4%). No significant association was detected between sex and hypermobility. Joint hypermobility was inversely correlated with age and BMI. Scoliosis was found in 43 subjects (5.2%) and all of them except one girl had mild scoliosis. The most common scoliosis pattern was a single left thoracolumbar curve. Seventy-three subjects (8.9%) had Cobb angle under 10°, with a potential for progression. Among subjects having GJH, the most common clinical finding was pes planus (34.3%) and the most common clinical symptom was ankle sprain (31.3%). Conclusion: Similar to that found in children from many countries, GJH is a common clinical condition in Turkish children. GJH should be assessed in the differential diagnosis of adolescents with musculoskeletal complaints for effective treatment and reducing morbidity. GJH should be considered in adolescents with scoliosis, which may be an important aspect in treatment.